2018
DOI: 10.3390/bioengineering5030052
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Gellan Gum-Based Adipose-Like Microtissues

Abstract: Adipose tissue is involved in many physiological processes. Therefore, the need for adipose tissue-like analogues either for soft tissue reconstruction or as in vitro testing platforms is undeniable. In this work, we explored the natural features of gellan gum (GG) to recreate injectable stable adipose-like microtissues. GG hydrogel particles with different percentages of polymer (0.5%, 0.75%, 1.25%) were developed and the effect of obtained mechanical properties over the ability of hASCs to differentiate towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
3
3
0
Order By: Relevance
“…1) for the chondrogenic differentiation. In regards to the PPAR-γ responses, the observed trend, overall slight yet detectable, also supports previous results concerning the adipogenic differentiation in soft GG hydrogels 27 .…”
Section: Please Do Not Adjust Marginssupporting
confidence: 90%
“…1) for the chondrogenic differentiation. In regards to the PPAR-γ responses, the observed trend, overall slight yet detectable, also supports previous results concerning the adipogenic differentiation in soft GG hydrogels 27 .…”
Section: Please Do Not Adjust Marginssupporting
confidence: 90%
“…In sum, all suggest that GG is a suitable material for encapsulation, adipogenic differentiation, and maintenance of human primary ASCs. This was also demonstrated by another study which has shown the development of adipose-like microtissues based on GG [61]. Like us, they have shown successful adipogenic differentiation of encapsulated ASCs in different GG concentrations.…”
Section: Discussionsupporting
confidence: 74%
“…Micro-tissues engineering for adipose/breast have been explored by several groups. Most of them constructed adipose-like micro-tissues in vitro [ [19] , [45] ]. Hoefner, C cultured self-assembly ADSC spheroids using the liquid overlay technique and evaluated the ECM of differentiated ADSC spheroids, which was proved to be similar to native adipose [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hoefner, C and co-workers cultured ADSCs spheroids and found that their ECM mainly consisted of fibronectin, collagen V, and VI and shifted into laminin, collagen I, IV, V and VI after adipogenic induction in vitro, like ECM in native adipose tissue [ 17 ]. Some ADSCs micro-tissues were fabricated and lipid accumulation were observed in vitro [ [18] , [19] , [20] ]. However, when it comes to animal experiments, single adipose micro-tissues are easy to result in adipose tissue atrophy and fibrosis due to insufficient vascularization [ 18 ].…”
Section: Introductionmentioning
confidence: 99%